INTRAVENOUS IMMUNOGLOBULINS: MECHANISMS OF THERAPEUTIC EFFECTS - V. A. Lazanovich; E. V. Prosekova (Медицинская иммунология, 2014)
Intravenous immunoglobulins (IVIG) are currently the most widely used immunobiological drug derived from donor blood. The IVIG preparations contain antibodies, mostly, of IgG class, obtained from plasma pools of 3,000 to 15,000 donors (over 1000 donors per lot, according to international standards and guidelines), being used for treatment of various diseases over four last decades. Initially, IVIG application wasaimed for immune support only in primary immunodeficiency states. However, recent clinical and experimental data show effectiveness of the IVIG in systemic and autoimmune diseases, immune-associated infertility and miscarriage. As well as in translantology, hematology and other fields of medicine. Their efficiency is associated with immunomodulatory effects. There is a growing number of publications bearing on this subject and elucidating possible mechanisms of therapeutic effects of IVIG, which are based on the latest basic and clinical research findings in this area. At the same time, much issues remain unclear and contradictory, and some data are mutually exclusive, thus prompting further studies and trials of IVIG preparations. The aim of this article is to summarize the known basic mechanisms of therapeutic effects, main results of recent research in this area,and potential clinical applications of IVIG in future.